Beyond the Green Deal: Upgrading the EU's energy diplomacy for a new era - Maria Pastukhova; Jacopo Maria Pepe; Kirsten Westphal (Stiftung Wissenschaft und Politik (SWP), 2020)
The Green Deal launched by the new Commission in 2019 is set to profoundly reshape the European Union (EU)'s energy diplomacy. However, although the EU will have to adapt to the new policy direction determined by the Green Deal, it cannot be reduced to it. The EU's energy diplomacy will need to cope with the profound and various geo‑economic and geopolitical shifts set in motion by the energy transition, which include - but even transcend - the Green Deal's goals. The current EU Energy Diplomacy Action Plan is due for revision. In setting the new priorities, the Union will need to strike a balance between global aspirations and limited financial means. The upcoming German EU Presidency is being called to step up its efforts to upgrade the EU's energy diplomacy along three lines. First, review the existing set of priorities according to the new challenges. Second, expand the geographic radius of its actions beyond its direct neighborhood by focusing on 12 anchor partners along the Afro-Eur-Asian ellipse. Third, upgrade its instruments toolbox along five new areas of action, avoiding an exclusively normative-ideological approach in favor of a more realistic and country-tailored one.
Keywords: 320